Shifting ground: agricultural R&D worldwide - Pardey, Philip G.; Alston, Julian M.; Piggott, Roley R. (International Food Policy Research Institute, 2006)
This brief summarizes the book, Agricultural R&D in the Developing World: Too Little, Too Late?, edited by Philip G. Pardey, Julian M. Alston, and Roley R. Piggott. The authors of the brief look at topics such as: International spillovers of public agricultural R&D; patterns of worldwide public investments in agricultural research; pervasive underfunding of agricultural research; divergent research agendas. The brief examines policy implications and concludes that "The issues are large scale and long term and demand serious attention, including further, more specific analysis. The national governments of developing countries can take some initiative, as indicated by the analysis of case studies in the book, in areas of national agricultural research policy such as: (1) enhancing IPR and tailoring the institutional and policy details of intellectual property to best fit local circumstances, (2) increasing the total amount of government funding for their national agricultural research systems, (3) introducing institutional arrangements and incentives for private and joint public–private funding, such as matching grants and check-off funds, and (4) improving the processes by which agricultural research resources are administered and allocated.